Microbiological quality of mare's milk and trends in chemical composition by comparison of different analytical methods - Končurat, Ana (Array, 2019)
In this study the quality of Croatian coldblooded mare’s milk during six months lactation period was investigated. Samples of milk were collected throughout six month’s lactation, from 22 mares and included three consecutive lactations. Physicochemical properties (pH, °SH, density) and chemical composition of raw mare milk have been studied. Fat, lactose, protein and solid non fat contents were analysed by infrared spectrophotometry and by conventional methods. Somatic cell count and microbiological parametres such as the total bacterial count, Enterobacteriaceae, coagulase positive staphylococci as well as presence of pathogens, Salmonella species and Listeria monocytogenes were also researched. Results are presented as comparison of standard and instrumental methods for chemical analysis (fat, protein, solid non fat, lactose). The mean values are presented as trends during lactation. Results were analysed by Stata 10.0. For results obtained by using different methods there were significant differences between methods for milk fat on 10th day, lactose content on 10th and 60th day, and total solids non fat on 60th day of lactation. Values of milk fat, protein, lactose and solids non fat obtained on the 40th, 60th, 120th and 180th days of lactation by IR spectrometry were compared with the value obtained on the 10th day of lactation by the same method (IR spectrometry). Milk of the Croatian coldblooded mares showed stabile chemical composition for all ingredients except lactose (p=0.0001), and high microbiological quality throughout the lactation period.